Keragaan Agronomi dan Kelayakan Usahatani Beberapa Varietas Padi Sawah (Oryza sativa L.) dengan Sistem Tanam Tegel di Desa Ajee Rayeuk Kecamatan Ingin Jaya Aceh Besar. - Nadi Ainina; Husaini Husaini; Dewi Junita; Muhammad Jalil; Mawaddah Putri Arisma Siregar (Universitas Teuku Umar, 2022)
Superior varieties and cropping systems are very influential on rice production. The use of cropping systems is used to obtain optimal plant growth and to increase farmers' yields and income. This study aimed to determine the effect of the tegel planting system on agronomic performance and the feasibility of farming on several high-yielding rice varieties in Ajee Rayeuk Village, Ingin Jaya Subdistrict, Aceh Besar. The sampling method was carried out experimentally and field surveys using a randomized block design (RBD) with 3 replications per variety, one variety contained 9 samples, the varieties used were Ciherang, Siliwangi, Suluttan. The parameters observed in this study were agronomic performance parameters. in the form of plant height, number of tillers, weight of grain per clump, weight of 1000 grains, weight of empty grain and weight of filled grain. Farming analysis parameters include income and production costs. Observational data were analyzed using ANOVA analysis and farming analysis. The results showed that the tegel planting system in 3 rice varieties had a significant effect on the agronomic performance of rice plants, and farming on Suluttan variety was feasible to be applied by lowland rice farmers in Ajee Rayeuk Village. Varieties had a significant effect on the agronomic performance of rice plants on the parameters of plant height and number of tillers. The best agronomic performance and farming analysis were found Suluttan variety.